PENINGKATAN DAYA SAING UMKM MELALUI STRATEGI BRANDING YANG EFEKTIF DAN INOVATIF - Kuncara, Tommy; Ariyanto, Ariyanto; Immi Fiska Tarigan; Sri Wahyu Handayani (Asosiasi Dosen Muda Indonesia, 2024)
Enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) is a key focus in supporting national economic growth. This community service program aims to provide training and guidance for MSME actors on effective and innovative branding strategies to improve their ability to compete in local and national markets. The program is a collaboration between Gunadarma University and the Indonesian Association of Young Lecturers (ADMI), conducted during the PTA 2024/2025 academic year through online and offline sessions. The program integrates the university's expertise in Information and Communication Technology (ICT), involving four faculties and ten related disciplines, such as information systems, accounting, and communication studies. The training includes digital branding, brand identity management, and technology-based marketing strategies. This program is expected to enhance the skills of MSME actors in building competitive brands and produce outputs such as scientific publications, activity documentation, and increased lecturer participation in community service initiatives.